PENINGKATAN KEMAMPUAN DIGITAL MARKETING PELAKU USAHA DI DESA WISATA BEJIHARJO - Iis Prasetyo; Akhmad Rofiq; Adin Ariyanti Dewi; Firmansyah Firmansyah (LPPM Universitas Nusa Mandiri, 2025)
Bejiharjo Tourism Village, located in Karangmojo Subdistrict, Gunungkidul Regency, possesses significant natural and cultural tourism potential. However, limited capacity among local business actors in utilizing digital marketing has hindered the optimal promotion of tourism products. Properly managed, this tourism potential could drive various aspects of community development, particularly in the economic sector, and contribute to local welfare. Effective tourism management relies on the ability of managers to package and present these potentials in ways that positively support community empowerment in Bejiharjo Village. In response to this condition, a community service program was implemented with the theme of enhancing the digital marketing skills of local business actors. The objective was to raise awareness and improve the ability of these actors to utilize digital marketing for promoting tourism products, an increasingly vital skill in the context of global competition. The program was carried out through planning, implementation, evaluation, and follow-up stages. Training employed adult learning methods, combining lectures, discussions, and hands-on practice, with a focus on social media-based promotion strategies. The results indicated high participant enthusiasm during training and mentoring sessions, improved understanding of digital platforms, and greater awareness of the importance of technology-based marketing. Some participants began applying social media management to promote their products, although further assistance remains necessary. This program demonstrates that digital marketing training can serve as an effective strategy to strengthen the marketing capacity of tourism village entrepreneurs, ultimately contributing to tourism development and the improvement of local community welfare.